Práctica intercultural de los becarios de La Fundación Hanns Seidel - Ecuador - Llasag, Milton (2001)
Intercultural practice Fellows the Hanns Seidel Foundation - Ecuador. Problem Statement. Delimitation of the problem. Social-organizational processes of indigenous peoples. Consideracioens osciales and indigenous economic sector. The indigenous movement and intercultural approach. The Hanns Seidel Foundation. Mission. Bases overseas development policy. Development aid and cultural policy. The Hanns Seidel Foundation inthe Ecuador. Fellows of the Foundation and its contribution to the construction of an intercultural society. Justification. Goals. General purpose. Specific objectives. Theoretical basis: Visions of multiculturalism. Background. Multiculturalism. Multiculturalism and identity building. Multiculturalism from the point of view of language and culture. Intercultural recognition of the values ​​of the other. Scientific multiculturalism. Intercultural since the conflict. Population and sample. Techniques